How can corporate culture contribute to emission reduction in the construction sector? An SME case study on beliefs, actions, and outcomes - Carmen Isensee; Frank Teuteberg; Kai-Michael Griese (Corporate Social Responsibility and Environmental Management, 2022)
In the race against climate change, small and medium-sized enterprises (SMEs) play a fundamental role. To clarify the contribution of corporate culture to SMEs' emission reduction, three perspectives can be useful: corporate culture as driver and barrier, current and planned corporate culture development actions, and the corporate culture profile as an outcome. As the first application of the extended Belief-Action-Outcome framework, this single case study exemplifies the role of corporate culture in an SME from the steel construction and manufacturing sector in Germany. The investigated SME has achieved emission reduction while increasing its revenue and is an early adopter of sustainable and digital development. The rich insights from an employee survey, semi-structured interviews, observation, and document analysis allowed us to outline an informed approach toward corporate culture development that emphasizes vision development of the desired corporate culture and the role of information systems for promoting emission reduction.
Keywords: 650; belief-action-outcome framework; corporate culture; digitalization; emission reduction; sustainability culture; sustainable development